2002
DOI: 10.1007/s00431-001-0909-1
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural hearing loss as an extra-intestinal manifestation of ulcerative colitis in an adolescent girl with pyoderma gangrenosum

Abstract: Although pyoderma gangrenosum is well described with inflammatory bowel disease, sensorineural hearing loss a is very unusual finding, possibly of auto-immune aetiology. We recommend steroid or immunosuppressive therapy in such a patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The auditory system can become the target of an autoimmune attack in two ways, primary autoimmune disease of the inner ear and secondary involvement by systemic autoimmune diseases including vasculitides, systemic lupus erythematosus, Cogan's syndrome, Wegener granulomatosis, and rheumatoid arthritis (3,4). Several case presentations have been published reporting acute hearing loss, which is thought to be immune-mediated, during the course (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), or as an early manifestation, of IBD (15). In these patients, sensorineural hearing loss (SNHL), usually with bilateral involvement, developed suddenly and deteriorated rapidly over weeks or months, particularly in the active period of the bowel disease as well as the quiescent period.…”
mentioning
confidence: 97%
“…The auditory system can become the target of an autoimmune attack in two ways, primary autoimmune disease of the inner ear and secondary involvement by systemic autoimmune diseases including vasculitides, systemic lupus erythematosus, Cogan's syndrome, Wegener granulomatosis, and rheumatoid arthritis (3,4). Several case presentations have been published reporting acute hearing loss, which is thought to be immune-mediated, during the course (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), or as an early manifestation, of IBD (15). In these patients, sensorineural hearing loss (SNHL), usually with bilateral involvement, developed suddenly and deteriorated rapidly over weeks or months, particularly in the active period of the bowel disease as well as the quiescent period.…”
mentioning
confidence: 97%
“…Most data on this association have been reported as single case reports [7][8][9][10][11], and few studies that investigated patient series [12][13][14] suggested that pauci-or asymptomatic SNHL may be found in up to about 40 % of UC patients. Since the clinical course of hearing loss is independent from that of UC, and if the disorder is not recognized, it causes permanent hearing loss, and it has been suggested that it is important to identify SNHL in its early phases [12].…”
Section: Discussionmentioning
confidence: 95%
“…The latter may include sensorineural hearing loss (SNHL) [4], i.e., sudden or progressive hearing impairment due to the degeneration of various components of the cochlea [5], which was first associated with IBD by Levitan in 1973 [6]. Since then, SNHL in UC has been mainly described as single case reports [7][8][9][10][11], and the few studies conducted on series of patients with IBD have demonstrated that this condition is more prevalent (although often with subclinical manifestations) in adult UC patients [12][13][14], whereas it has not been found in pediatric IBD series [15].…”
Section: Introductionmentioning
confidence: 99%
“…Management of these patients including diagnosis and treatment is generally similar to patients without UC (Pandian, Pawar et al, 2004). O t h e r r a r e n e u r o l o g i c a l c o m p l i c a t i o n s o f U C t h a t h a v e b e e n r e p o r t e d i n c l u d e : a c u t e disseminated encephalomyelitis, optic neuritis, sensorineural hearing loss, myelopathy, peripheral polyneuropathy, Guillain-Barre syndrome, and myasthenia gravis (Gondim et al, 2005;Kanra et al, 2002;Krystallis et al, 2010;Lossos et al, 1995;Scheid & Teich, 2007;Tan, 1974;Yesilova et al, 2006). Many of these complications are autoimmune in nature and respond to steroids and/or immunosuppressive therapy.…”
Section: Immune Mediated Neuropathymentioning
confidence: 99%